Modeling And Energy Analysis of An Educational Building by Autodesk Insight and Green Building Studio - Mehedi, Hasan; Md. Tarikul, Islam (INTI International University, 2026)
Buildings consume substantial energy throughout their life cycle, contributing significantly to global warming and environmental degradation. To address this challenge, early-stage energy performance assessment is critical. This study applies a BIM-based energy modeling methodology to predict and analyze the energy performance of a multi-storied educational (library) building located in Gulshan-2, Dhaka, Bangladesh, with a total floor area of approximately 8,830 m². The research methodology integrates Autodesk Revit 2021 for building modeling and Autodesk Insight, a cloud-based energy analysis tool, to evaluate electricity, fuel, and water consumption at the conceptual design stage. The results indicate a total Energy Use Intensity (EUI) of 94.8 kWh/m²/year and a mean annual energy cost of 7.06 USD/m²/year. Detailed parametric analysis reveals that HVAC systems (18.03 kWh/m²/year), plug load efficiency (38.21 kWh/m²/year), and lighting efficiency (38.57 kWh/m²/year) are the dominant contributors to overall energy consumption. Envelope-related parameters such as window-to-wall ratio, shading, glazing, wall construction, and roof construction exhibit comparatively lower but measurable impacts, with orientation-specific variations across the north, south, east, and west facades. The significance of this study lies in demonstrating the effectiveness of BIM-based energy analysis for early-stage decision-making in tropical climates. The findings provide quantitative insights into key energy drivers and highlight priority areas for optimization, enabling designers and policymakers to implement cost-effective and climate-responsive energy strategies. This approach supports sustainable educational building design in rapidly urbanizing contexts such as Bangladesh